Salicylic acid improves cowpea productivity under water restriction in the field by modulating metabolism - Cavalcante, Igor Eneas; de Melo, Alberto Soares; Ferraz, Rener Luciano de Souza; de Alencar, Rayanne Silva; Dias, Guilherme Felix; Viana, Priscylla Marques de Oliveira; Rocha, Maurisrael Moura; Ndhlala, Ashwell Rungano; Sá, Francisco Vanies da Silva; de Lacerda, Claudivan Feitosa; Viégas, Pedro Roberto Almeida (Frontiers in Plant Science, 2024)
Introduction Salicylic acid has shown promise in alleviating water stress in cultivated plants. However, there is a lack of studies confirming its effectiveness in cowpea plants grown in field conditions. Therefore, this research aimed to evaluate the use of salicylic acid as a water stress mitigator in cowpea cultivars under different irrigation depths in field conditions. Methods Four cowpea cultivars (BRS Novaera, BRS Tapaihum, BRS Pujante, and BRS Pajeú) were subjected to different treatments: control (W100: 100% replacement of crop evapotranspiration – ETc), W50 (50% of ETc), W50+SA2 (50% of ETc + 276 mg L-1 of SA), and W50+SA4 (50% of ETc + 552 mg L-1 of SA). The treatments were combined in a 4×4 factorial scheme with three replications, arranged in a randomized block design. Results Water restriction had a negative impact on the water status, growth, gas exchange, and production of the cultivars while also leading to changes in the antioxidant metabolism and osmolyte concentration. The application of SA enhanced antioxidant activity and the synthesis of osmotic adjusters under stress conditions. The most effective concentration was 276 mg L-1 in stage R2 and 552 mg L-1 in stage V7, respectively. The BRS Pujante cultivar showed increased productivity under water restriction with SA application, while the BRS Tapaihum was the most tolerant among the cultivars studied. Discussion In summary, our findings underscore the importance of using SA to mitigate the effects of water restriction on cowpea cultivation. These discoveries are crucial for the sustainability of cowpea production in regions susceptible to drought, which can contribute to food security. We further add that the adoption of new agricultural practices can enhance the resilience and productivity of cowpea as an essential and sustainable food source for vulnerable populations in various parts of the world.